OILY WASTE WATER BY MEANS OF ORGANO - , Г. И., В. В. (Municipal economy of cities (Technical science), 2013)
The results of studies on the treatment of wastewater containing oil products, using as a sorbent - clay, modified distillation residues distillation of caprolactam.